Molecular diagnosis of endometrial cancer from uterine aspirates. Issue 10 (21st June 2013) - Perez‐Sanchez, Cristina; Colas, Eva; Cabrera, Silvia; Falcon, Orlando; Sanchez‐del‐Río, Angel; García, Enrique; Fernández‐de‐Castillo, Luis; Muruzabal, Juan Carlos; Alvarez, Elena; Fiol, Gabriel; González, Carmen; Torrejón, Rafael; et al.
Abstract : Rapid and reliable diagnosis of endometrial cancer (EC) in uterine aspirates is highly desirable. Current sensitivity and failure rate of histological diagnosis limit the success of this method and subsequent hysteroscopy is often necessary. Using quantitative reverse transcriptase‐polymerase chain reaction on RNA from uterine aspirates samples, we measured the expression level of 20 previously identified genes involved in EC pathology, created five algorithms based on combinations of five genes and evaluated their ability to diagnose EC. The algorithms were tested in a prospective, double‐blind, multicenter study. We enlisted 514 patients who presented with abnormal uterine bleeding. EC was diagnosed in 60 of the 514 patients (12%). Molecular analysis was performed on the remnants of aspirates and results were compared to the final histological diagnoses obtained through biopsies acquired by aspiration or guided by hysteroscopy, or from the specimens resected by hysterectomy. Algorithm 5 was the best performing molecular diagnostic classifier in the case–control and validation study. The molecular test had a sensitivity of 81%, specificity of 96%, positive predictive value (PPV) of 75% and negative predictive value (NPV) of 97%. A combination of the molecular and histological diagnosis had a sensitivity of 91%, specificity of 97%, PPV of 79% and NPV of 99% and the cases that could be diagnosed on uterine aspirate rose from 76 to 93% when combined with the molecular test. Incorporation of the molecular diagnosis increases the reliability of a negative diagnosis, reduces the need for hysteroscopies and helps to identify additional cases. Abstract : What's new? Many studies report biomarker discovery using omics approaches, but few survive the translation into clinically validated diagnostic assays. Using previously identified biomarkers, here the authors set to improve the early diagnosis of endometrial cancer (EC) based on minimally invasive samples: endometrial aspirates. Current sensitivity and failure rate of histological diagnosis limit the success of aspirate‐based diagnosis and subsequent hysteroscopy is often necessary. The authors developed and clinically validated a novel molecular test, which increases the efficacy, sensitivity and negative predictive value of aspirate‐based diagnosis and has the potential to reduce the average time and cost for EC diagnosis.